Synthesis of Dimeric Hybrid Steroid Trioxadispiroketals by Cadiot–Chodkiewicz Coupling/Gold-Catalyzed Dispiroketalization - Jorge, Victoria-Miguel; Flores-Álamo, Marcos; Iglesias-Arteaga, Martin A. (Synthesis, 2025)
Two hybrid steroids dimers bearing the trioxadiespiroketal moiety were obtained starting from cholesterol and diosgenin. The key steps of the designed protocol are the Cadiot–Chodkiewicz cross coupling between iodoalkynols and alkynols and the Au-catalyzed dispiroketalization of hybrid dialkyndiols.
Keywords: hybrid steroid dimers; trioxadispiroketals; palladium catalysis; gold catalysis; NMR; X-ray diffraction